Penerapan Model Kooperatif Tipe Think Pair Share (TPS) Pada Pembelajaran Tematik Terpadu di Kelas IV Sekolah Dasar - Meyda Putri; Elfia Sukma (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2022)
This study aims to get a real picture of the implementation of the cooperative model Think Pair Share (TPS) by the teacher in integrated thematic learning for fourth grade students of elemtary school. The TPS learning steps used by the teacher in integrated thematic learning, as well as the efforts made by the teacher to overcome the obstacles that arise in the TPS model for the implementation of integrated thematic learning. This research is a descriptive study with a qualitative approach. The research subjects were fourth grade teachers and fourth grade students of elemtary school. The analysis technique used in this research is a descriptive analysis model consisting of data collection, data organizing, data management, data verification and interpretation, and conclusions. Then the data validity technique used is the method and source triangulation technique. Based on the research that has been done, it is found that the cooperative model of the Think Pair Share type is very effective in the integrated thematic learning process seen from the use of learning steps consisting of Thinking, Pairing and Sharing where this model uses groups. learning in pairs which provides opportunities to think and provides opportunities for students to exchange opinions.